Cost Measurement Research Trends: A Bibliometric Analysis - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study examines the development and intellectual structure of cost measurement research using a bibliometric approach. Cost measurement has long been a fundamental component of accounting and managerial decision-making, yet its evolution reflects increasing complexity driven by technological advancements and interdisciplinary integration. This research analyzes a collection of scientific publications retrieved from major academic databases, employing bibliometric techniques such as co-occurrence analysis, network visualization, and thematic mapping using VOSviewer. The results reveal that cost effectiveness remains the central theme connecting diverse research streams, including traditional cost analysis, healthcare evaluation, and scientific measurement practices. Over time, the field has shifted toward incorporating advanced analytical approaches such as machine learning, optimization, and uncertainty analysis, indicating a transition toward more data-driven and predictive models. Furthermore, the findings highlight strong interdisciplinary linkages across accounting, engineering, and health sciences, as well as growing attention to methodological rigor through concepts such as reliability, calibration, and reproducibility. This study contributes by providing a structured overview of research trends and identifying emerging directions, offering valuable insights for future studies in cost measurement and decision-support systems.